Substance Checking Outreach and PrEP Engagement (SCOPE) Study: protocol for a non-randomised clinical trial in Baltimore, Maryland USA - Susan G Sherman; Saba Rouhani; Kristin E Schneider; Danielle Friedman Nestadt; Emily M Martin; Miles Morris; Brian W Weir (BMJ Open, 2025)
Introduction As the opioid crisis continues, people who use drugs (PWUD) experience a disproportionate burden of both HIV and overdose, driven by increased injection-related HIV outbreaks and an opaque and rapidly evolving drug market, respectively. Pre-exposure prophylaxis (PrEP) for HIV and point-of-care drug checking services are underused yet potentially impactful interventions to address the harms of the opioid crisis. Implementing such interventions using known strategies to enhance client engagement and reduce access barriers, such as street outreach, mobile services and peer navigation, can optimise intervention and maximise their impact.Methods and analysis The Substance Checking Outreach and PrEP Engagement (SCOPE) Study is a non-randomised clinical trial evaluating the impact of the Check It intervention, a mobile community PrEP and drug checking intervention in Baltimore, Maryland, USA. SCOPE will recruit a cohort of 500 PWUD at risk for HIV through street-based recruitment methods. Cohort members will be followed semi-annually for 18 months. The primary study outcomes are engagement with the PrEP continuum of care and the number of non-fatal overdoses. We will use both random effects models and marginal structural models to estimate the effects of Check It on participant engagement on the PrEP continuum and the number of non-fatal overdoses over time.Ethics and dissemination Study procedures have been approved by the Johns Hopkins Bloomberg School of Public Health Institutional Review Board. Risks to participants are low, with the most serious risk being potential data confidentiality breaches. This risk was minimised through the use of secure data storage platforms with limited user access. Study findings will be disseminated through peer-reviewed manuscripts, academic presentations, and reports and fact sheets designed for lay audiences.Trial registration number This study was registered with clinicaltrials.gov (study ID: NCT05977881; Protocol ID: 00017498).